Representation of Hindu–Buddhist Heritage in the Kotta Cinna Site Museum: The Politics of Memory and Early Historical Identity - Hardiyansyah, Muhammad Ricky; Nababan, Surya Aymanda; Putri, Audy Amalia (Warisan: Journal of History and Cultural Heritage, 2026)
This article examines the representation of Hindu–Buddhist heritage in the Museum Situs Kotta Cinna and its role in shaping memory politics and early historical identity in North Sumatra. The study asks how Hindu–Buddhist remains are curated and narrated, and what form of historical identity is constructed through these practices. Using a qualitative approach that combines site observation, exhibition analysis, archival research, and interviews with museum stakeholders, the study applies theories of memory and identity to interpret curatorial strategies and narrative framing. The findings show that the museum selectively presents Kotta Cinna as evidence of an early cosmopolitan polity shaped by transregional networks while integrating it into contemporary local and national identity discourses. This process reflects how archaeological objects are transformed into symbolic capital for regional pride and historical legitimacy. The study contributes by demonstrating that museum representation functions as an active mechanism of memory production rather than mere preservation, offering a clearer framework for understanding the role of heritage institutions in constructing early Sumatran identity.